2005
DOI: 10.1007/s00213-005-0084-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of caffeine on performance and mood: withdrawal reversal is the most plausible explanation

Abstract: Appropriately controlled studies show that the effects of caffeine on performance and mood, widely perceived to be net beneficial psychostimulant effects, are almost wholly attributable to reversal of adverse withdrawal effects associated with short periods of abstinence from the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
297
2
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(322 citation statements)
references
References 51 publications
16
297
2
4
Order By: Relevance
“…If caffeine was consumed, the adverse effects of lowered alertness and headache were avoided, but even after 100 + 150 mg of caffeine their alertness was not raised above the level of alertness showed by nonconsumers of caffeine (group N) who received placebo (Figure 1, middle panel). This result is similar to that from an early study comparing responses to caffeine of coffee drinkers and abstainers (Goldstein et al, 1969), and is consistent with the claim, supported by a variety of subsequent findings, that regular caffeine consumption provides little or no net benefit for alertness or performance on tests of vigilance (James and Rogers, 2005;Sigmon et al, 2009). Another interpretation could be that frequent caffeine consumers are 'constitutionally' less alert or more fatigued, and they use caffeine to remedy this state of affairs.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…If caffeine was consumed, the adverse effects of lowered alertness and headache were avoided, but even after 100 + 150 mg of caffeine their alertness was not raised above the level of alertness showed by nonconsumers of caffeine (group N) who received placebo (Figure 1, middle panel). This result is similar to that from an early study comparing responses to caffeine of coffee drinkers and abstainers (Goldstein et al, 1969), and is consistent with the claim, supported by a variety of subsequent findings, that regular caffeine consumption provides little or no net benefit for alertness or performance on tests of vigilance (James and Rogers, 2005;Sigmon et al, 2009). Another interpretation could be that frequent caffeine consumers are 'constitutionally' less alert or more fatigued, and they use caffeine to remedy this state of affairs.…”
Section: Discussionsupporting
confidence: 86%
“…However, although frequent consumers feel alerted by caffeine, especially by their morning tea, coffee, or other caffeine-containing drink, evidence suggests that this is actually merely the reversal of the fatiguing effects of acute caffeine withdrawal (James and Rogers, 2005;Sigmon et al, 2009). That is, little or perhaps no net benefit for alertness is gained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, in the nondeprived condition, nicotine produced modest enhancement of attentional and computational performance beyond baseline. This issue of primary enhancement vs withdrawal relief has been central to the debate on the performance effects of nicotine (Heishman et al, 1994;Hughes, 1991) and other psychomotor stimulants (James and Rogers, 2005;Koelega, 1993). In this study, we tested the same smokers after overnight tobacco deprivation and during ad libitum smoking, which allowed an unequivocal determination that nicotine normalized deprivation-induced deficits and enhanced cognitive abilities in the nondeprived condition.…”
Section: Discussionmentioning
confidence: 99%
“…By selecting these subjects, we minimized variability related to caffeine tolerance, or, if the subjects had been required to abstain from caffeine, caffeine withdrawal. However, some have argued that a sample of light infrequent caffeine consumers is not representative of the general population and that these individuals may be self-selecting due to heightened sensitivity to adverse effects of caffeine including anxiety (James and Rogers, 2005). In fact, both the positive and negative subjective, and also physiological effects of caffeine in the present study were similar to those previously reported in other populations (Evans and Griffiths, 1991;Griffiths et al, 1990;Hughes, 1996) and there was little evidence that these samples were more sensitive to the aversive effects of caffeine (Childs and de Wit, 2006).…”
Section: Gene Polymorphisms and Caffeine Anxiety E Childs Et Almentioning
confidence: 99%